Edukasi Online Pelaksanaan Aktifitas Fisik Pada Pasien Diabetes Melitus Di Masa Pandemi Covid-19 - Weny Amelia; Fitria Alisa; Lenni Sastra; Lola Despitasari (Lembaga Layanan Pendidikan Tinggi Wilayah IX Sulawesi, 2020)
Diabetes mellitus (DM) is a chronic metabolic disorder characterized by high blood sugar levels as a result of insufficient insulin function caused by disruption of insulin products by beta Langerhans cells or the body's cells are less responsive to insulin. Covid-19 attacks almost all ages, especially people who have a history of chronic disease (co-morbid) have a risk of getting it more frequently and with worse complications from this disease. One of the chronic disease history is DM. Physical exercise or physical activity is one of the pillars in the management of DM which functions to improve insulin sensitivity and also to maintain body fitness during the COVID-19 Pandemic. The form of community service activities carried out in the DM patient group includes education to patients and families about online education for DM sufferers during the COVID-19 pandemic. The results of community service activities obtained an increase in knowledge about the implementation of physical activity for DM patients during the COVID-19 pandemic.